Evaluación técnica y financiera para la producción de 4-isobutilacetofenona en Laboratorios Coaspharma S.A.S. (2020)
The project evaluates the technical-financial feasibility of the production of 4 isobutylacetophenone for Laboratorios Coaspharma S.A.S. For this, in the first instance, general issues regarding the company, ibuprofen, 4 isobutylacetophenone and different synthetic routes of the same, are addressed, to give the current context of the problem raised. In the same way, a diagnosis is made in thermodynamic terms to determine the thermodynamic feasibility of the reaction and its costs to be carried out in the laboratory. A multi-criteria selection matrix is ​​presented to choose a base document that provides the necessary information for the determination of reaction kinetics. With the selected data, the proposal of the possible adsorption models that the reaction can follow is made, then the deduction of the speed law and preliminary analysis of the reaction behavior are carried out, where the reaction is evaluated in an ideal case of a Batch reactor and the determination of the optimum operating temperature, among others. The proposal of the tubular reactor with heat exchange is made, based on the determined kinetic models and the financial analysis is carried out to determine the viability of the project, by evaluating the Net Present Value (NPV). Additionally, a pre-experimentation was carried out for the synthesis of 4 isobutylacetophenone by means of ibuprofen degradations, in order to evaluate other synthetic routes of the molecule. For the synthesis by acylation of Friedel-Crafts using beta zeolite, identification tests were performed by IR spectroscopy to the solid in addition to particle size tests, by sieving.